Administracyjnoprawny nadzór nad rynkiem bankowym na przykładzie wybranej działalności Komisji Nadzoru Finansowego - Wojcieszek, Mikołaj; Sułkowski, Karol (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The banking market is an extremely important part of the economy of each country, whose main task is to trade in financial resources. Therefore, it cannot remain unattended, which exercises the Financial Supervision Commission. Due to the huge role of supervision over the banking market, this article will be devoted to describing its operation. The aim of the elaboration will be to present and explain what supervision is, how it differs from control, what are the foundations of the activities of the Polish Financial Supervision Authority, what are its goals, tasks and scope of activity. The question of what instruments of influence the Commission is entitled to will also be taken into account.
Keywords: supervision; finances